2000
DOI: 10.1006/jath.1999.3410
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Partial Sums of Wavelet Series

Abstract: Given a distribution f belonging the Sobolev space H 1Â2 , we show that partial sums of its wavelet expansion behave like truncated versions of the inverse Fourier transform of f . Our result is sharp in the sense that such behavior no longer happens in general for H s if s<1Â2. Academic Press

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The results of Kelly et al [11,12] only assumed that the wavelets are bounded by radial decreasing 1 -functions. The behavior of wavelet expansions outside the Lebesgue set is discussed by Reyes [15], for 1 ≤ < ∞, whereas Kelly et al [11] proved that the wavelet expansion of a function in spaces converges pointwise everywhere on the Lebesgue set of a given function. Tao [16] has extended the results of Meyer [9] and Kelly et al [11,12] and showed that the wavelet expansion of any -function converges pointwise almost everywhere under the wavelet projections, hard sampling, and soft sampling summation methods, for 1 < < ∞.…”
Section: Introductionmentioning
confidence: 99%
“…The results of Kelly et al [11,12] only assumed that the wavelets are bounded by radial decreasing 1 -functions. The behavior of wavelet expansions outside the Lebesgue set is discussed by Reyes [15], for 1 ≤ < ∞, whereas Kelly et al [11] proved that the wavelet expansion of a function in spaces converges pointwise everywhere on the Lebesgue set of a given function. Tao [16] has extended the results of Meyer [9] and Kelly et al [11,12] and showed that the wavelet expansion of any -function converges pointwise almost everywhere under the wavelet projections, hard sampling, and soft sampling summation methods, for 1 < < ∞.…”
Section: Introductionmentioning
confidence: 99%